Urban Forest Conservation through the Lens of Ecological Exegesis: An Analysis of Surah Qaf: 9-11 - Wahyudin, Muhammad; Rifai, Abdusshomad (QiST: Journal of Quran and Tafseer Studies, 2026)
The escalating urban environmental crises, such as flooding and air pollution, demand beyond mere technical interventions; they require robust ethical-theological frameworks. While existing Islamic eco-theology predominantly discusses general environmental ethics, there is a distinct research gap in operationalizing specific Qur'anic verses into practical urban spatial policies. Therefore, this study aims to bridge classical theological interpretations of Surah Qaf: 9-11 with the modern regulatory concept of Green Open Space (RTH). Employing a qualitative library research design, this study utilizes the thematic exegesis (maudhu'i) approach formulated by Al-Farmawi. The primary data, sourced from authoritative classical commentaries (Ibn Kathīr, al-Rāzī, and Ibn 'Ashūr), were systematically analyzed using Abdullah Saeed's textual-contextual framework to synthesize classical theology with contemporary urban hydrology and microclimate science. The results indicate three key findings: (1) mā'an mubārakan (blessed water) aligns with sustainable urban hydrology and water security principles; (2) jannāt (gardens) serves as the theological equivalent of urban forests, functioning as vital ecosystem buffers and microclimate regulators; and (3) rizqan lil-'ibād (sustenance for servants) frames conservation not merely as a biological need, but as a socio-economic and spiritual mandate (amānah) for human stewardship (khalīfah). The novelty of this research lies in its specific formulation of "Ecological Piety," shifting the discourse from normative ethics to practical policy application. Ultimately, this study contributes a spiritual-ethical foundation for policymakers and fosters active community engagement in sustainable urban governance.